No grammatical gender effect on affective ratings: evidence from Italian and German languages. Issue 4 (19th May 2019) - Montefinese, Maria; Ambrosini, Ettore; Roivainen, Eka
ABSTRACT: In this study, we tested the linguistic relativity hypothesis by studying the effect of grammatical gender (feminine vs. masculine) on affective judgments of conceptual representation in Italian and German. In particular, we examined the within- and cross-language grammatical gender effect and its interaction with participants' demographic characteristics (such as, the raters' age and sex) on semantic differential scales (affective ratings of valence, arousal and dominance) in Italian and German speakers. We selected the stimuli and the relative affective measures from Italian and German adaptations of the ANEW (Affective Norms for English Words). Bayesian and frequentist analyses yielded evidence for the absence of within- and cross-languages effects of grammatical gender and sex- and age-dependent interactions. These results suggest that grammatical gender does not affect judgments of affective features of semantic representation in Italian and German speakers, since an overt coding of word grammar is not required. Although further research is recommended to refine the impact of the grammatical gender on properties of semantic representation, these results have implications for any strong view of the linguistic relativity hypothesis.